2019
DOI: 10.3892/or.2019.7310
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑203a‑3p is a candidate tumor suppressor that targets thrombospondin 2 in colorectal carcinoma

Abstract: The aim of the present study was to investigate the role of miR-203a-3p in colorectal cancer (CRC) and identify the target gene of microRNA (miR)-203a-3p. A total of 59 sets of cancer tissues and corresponding adjacent non-tumor tissues were collected from CRC patients (aged 31-78 years) between October 2016 and May 2017. Total RNA extraction and reverse transcription-quantitative polymerase chain reaction analysis, transfection assay, and Transwell and apoptosis assays, western blot analysis, a luciferase rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…In addition, PLEKHA7 re-expression results in the increased levels of miRNAs that we have previously identified to be regulated by PLEKHA7 in Caco2 cells, such as miR-30b, miR-200c, and miR-203a ( Figure 5I) [10,25]. These miRNAs are well-established tumor suppressors and are downregulated in many cancers, including colorectal tumors, as well as in colon cancer cell lines, such as those included in our study [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Together, these results are in agreement with our previous findings [10,25] and further support a tumor suppressing role for PLEKHA7 in the colonic epithelium, through recruitment and regulation of the RNAi machinery.…”
Section: Plekha7 Re-expression In Hct116 Cells Restores Junctional Lomentioning
confidence: 56%
“…In addition, PLEKHA7 re-expression results in the increased levels of miRNAs that we have previously identified to be regulated by PLEKHA7 in Caco2 cells, such as miR-30b, miR-200c, and miR-203a ( Figure 5I) [10,25]. These miRNAs are well-established tumor suppressors and are downregulated in many cancers, including colorectal tumors, as well as in colon cancer cell lines, such as those included in our study [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Together, these results are in agreement with our previous findings [10,25] and further support a tumor suppressing role for PLEKHA7 in the colonic epithelium, through recruitment and regulation of the RNAi machinery.…”
Section: Plekha7 Re-expression In Hct116 Cells Restores Junctional Lomentioning
confidence: 56%
“…Elevated ECM proteins in the tumor microenvironment increase the stiffness of the ECM, affecting cellular functions such as proliferation, adhesion, migration, tissue remodeling, and regulation of immune system [9][10][11]208]. [176,[179][180][181][182][183][184][185][186][187][188][189][190][191][192][193]195,196,[198][199][200][201][202]206] Collagen has important implications in the structural growth of tissue and regulates molecular signaling processes. A variety of tumors have been shown to overexpress collagen and its proteolytic components have been linked to increased invasiveness of tumors [41,84].…”
Section: Discussionmentioning
confidence: 99%
“…Differing from these results, Yosida et al reported that THBS2, regarded as an angiostatic factor, was significantly increased in CRC but not THBS1 [191]. In the opposite way to THBS1 regulation by miR-194, THBS2 has a binding domain in its 3 -untranslated region for miR-203a-3p, and downregulation of THBS2 by miR203a-3p inhibits CRC progression and metastasis [192]. There were also ambiguous results in terms of THBS2 expression such that low THBS2 expression reflected poor prognostic factors [193], while there was no correlation with improvement in metastatic colorectal cancer [194].…”
Section: Thrombospondinmentioning
confidence: 92%
“…However, Qian et al suggested that miR-203a-3p was downregulated in CRC tissues compared with adjacent normal tissues. miR-203a-3p served as a tumor suppressor of CRC cells by downregulating THBS2 expression [21]. Both studies used CRC cell lines SW480 and SW620, but their conclusions contradicted each other.…”
Section: Discussionmentioning
confidence: 96%